Metáforas del cuerpo ausente en las instalaciones de Doris Salcedo - Valesini, Maria Silvina (2016)
This work constitutes an advance of the doctoral thesis entitled “Latin American passable installations. The roles of the spectator against the poetics of the absent body “, led by Mss. Silvia Garcia. It proposes an approach to the Colombian artist Doris Salcedo, who explores the individual and collective memories testifying traumatic sociopolitical experiences inside the context in which they arise